High-fiber and low-glycemic index egg-roll cookies made from non-itchy taro (Colocasia esculenta var. Febi521) - Febi Nurilmala; Asmanur Jannah; Eny Palupi; Nia Sonani; Rita Mala; Naufal Muharam Nurdin; Fathimah Uswah Zahidah; Nila Salsa Bila; Sharannie; Shinta Anisa Dewi (Journal of Agriculture and Food Research)
Indigenous taro is a notable carbohydrate-rich food ingredient with significant dietary fiber. However, its natural itchiness has limited its widespread use. A new non-itchy variant, Febi521, was developed through in-vitro soma-clonal induction. This study aimed to create a high-fiber snack, specifically egg-roll cookies, using non-itchy taro (Colocasia esculenta var. Febi521). The cookies underwent comprehensive evaluation for their physical, chemical, and nutritional characteristics, including polyphenol content, glycemic index (GI), and glycemic load (GL). By fully substituting taro Febi521 flour in the recipe, we produced egg-roll cookies that were sensorially preferred, high in fiber (19.2 % wet basis), and had a low GI (39) and low GL (3). This formulation also met nutritional requirements for claims related to total fat, saturated fat, sodium, and cholesterol. Substituting taro flour increased fiber content threefold compared to wheat flour-based egg-roll cookies. This research highlights the potential of indigenous taro for diverse product development aimed at enhancing fiber intake among the population.